Synthesis of diastereomerically pure Lys(Nε‐lipoyl) building blocks and their use in Fmoc/tBu solid phase synthesis of lipoyl‐containing peptides for diagnosis of primary biliary cirrhosis1. (26th March 2015) - Rentier, Cédric; Pacini, Giulia; Nuti, Francesca; Peroni, Elisa; Rovero, Paolo; Papini, Anna Maria; Morelli, Giancarlo
<x xml:space="preserve">Abstract</x> Primary Biliary Cirrhosis is an immune‐mediated disease in which one of the epitopes recognized by antimitochondrial autoantibodies is a lipoylated fragment of the PDC‐E2 protein. Accordingly, the synthesis of lipoylated peptides as diagnostic tools is a relevant target. Up to now, the proper tools for the introduction of lipoylation on building blocks to be used in Fmoc/tBu solid phase peptide synthesis (SPPS) are lacking, and the role of chirality in lipoylation remains poorly studied. In this paper, we present the synthesis of lipoylated lysine derivatives as pure diastereomeric building blocks suitable for Fmoc/tBu SPPS and their introduction in relevant peptide sequences to possibly serve as synthetic probes for the development of novel diagnostic tools for this disease. The optimization of the synthesis of lipoylated building blocks derived from racemic, (R)‐, and (S)‐α‐lipoic acid is described. Synthesis of peptide probes incorporating lipoylation is described. An insight regarding the cleavage of lipoylated peptides is given, as well as a method to oxidize or reduce the 1, 2‐dithiolane ring of the lipoyl moiety directly on the peptide without any subsequent purification. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd.